NETWORK GOVERNANCE-BASED COMMUNICATION COORDINATION IN OVERCOMING JUVENILE DELINQUENCY: ANALYSIS OF SUPPORTING AND INHIBITING FACTORS IN ACEH TAMIANG DISTRICT (Pena Cendekia Insani, 2026)
This study analyzes communication coordination based on network governance in addressing juvenile delinquency in Aceh Tamiang Regency. The main focus of this study is to explain how inter-institutional communication is constructed, negotiated, and constrained in local government practice. This research employed a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with five key informants, field observation, and documentation studies. The findings show that the Youth and Sports Agency (Dispora) of Aceh Tamiang acts as the lead organization in a multi-actor communication network involving the police, schools, KNPI, and community leaders. Communication coordination has been established through formal forums and informal communication, but it remains suboptimal because the network is still centralized and not fully participatory. Supporting factors include regional policy support, stakeholder participation, and institutional resource availability. Meanwhile, inhibiting factors include weak cross-sectoral coordination, inter-institutional sectoral ego, budget constraints, and bureaucratic communication barriers. The novelty of this study lies in its analysis of inter-institutional communication within network-based youth development governance at the district level. This study emphasizes the need to strengthen more structured, inclusive, and sustainable communication coordination mechanisms to improve the effectiveness of juvenile delinquency prevention.